Serum levels of vitamin D are not associated with future risk of venous thromboembolism - Brodin, Ellen E.; Lerstad, Gunhild; Grimnes, Guri; Brækkan, Sigrid K.; Vik, Anders; Brox, Jan; Svartberg, Johan; Jorde, Rolf; Hansen, John-Bjarne (Thrombosis and Haemostasis, 2013)
Previous studies have provided indirect evidence for a possible association between vitamin D status and risk of venous thromboembolism (VTE). However, no study has so far investigated the association between serum levels of 25-hydroxyvitamin D (25(OH)D), the biomarker of vitamin D status, and risk of VTE. The aim of our study was to investigate whether high levels of 25(OH)D were associated with decreased risk of VTE in a prospective population-based study. Serum levels of 25(OH)D were measured in 6,021 men and women, aged 25–84 years, who participated in the Tromsø Study in 1994–1995. Incident VTE-events were registered from date of inclusion through the end of follow-up, September 1, 2007. Cox-regression models were used to calculate hazard ratios (HR) with 95% confidence interval (CI) for VTE. There were 201 incident VTE-events during a median of 10.7 years of follow-up. The risk of VTE did not decrease per one standard deviation (SD) (19.8 nmol/l) increase in serum 25(OH)D (multivariable HR 1.02; 95% CI 0.91–1.22). Moreover, subjects with serum 25(OH)D ≥ 70 nmol/l (upper quartile) did not have decreased risk of VTE compared to those ≤ 44 nmol/l (lower quartile) in age- and sex-adjusted analysis (HR 0.91, 95% CI: 0.60–1.37, p for trend across quartiles 0.9) or multivariable analysis adjusted for age, sex, body mass index, smoking, and physical activity (HR 0.76, 95% CI: 0.45–1.28, p for trend across quartiles 0.9). Subgroup analyses showed no associations between serum levels of 25(OH)D and unprovoked or provoked VTE. In conclusion, in our study, normal serum levels of 25(OH)D were not associated with future risk of VTE, suggesting that vitamin D status does not play an important role in the pathogenesis of VTE. However, our findings did not apply to subjects with vitamin D deficiency (< 30 nmol/l) due to lack of statistical power among these subjects.
Keywords: Deep-vein thrombosis; epidemiological studies; hormones